1999
DOI: 10.1038/sj.bjc.6690351
|View full text |Cite
|
Sign up to set email alerts
|

Urinary concentrations of the soluble adhesion molecule E-cadherin and total protein in patients with bladder cancer

Abstract: Summary Reduced expression of the adhesion molecule E-cadherin has been associated with increased invasiveness and poorer survival in patients with bladder cancer. We have examined soluble E-cadherin (sE-cadherin) and total protein concentrations in urine from patients with bladder cancer (n = 34), non-neoplastic benign urological diseases (n = 14) and healthy controls (n = 21) to determine their diagnostic and prognostic significance. Soluble E-cadherin concentrations of the cancer group were significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
(48 reference statements)
0
22
0
2
Order By: Relevance
“…The soluble cleaved form of E-cadherin has been observed in serum under non-pathological conditions, but increased levels of the soluble form have been detected in patient peripheral blood samples 24,54 and urine samples 55 in a variety of diseases. 21 It has been suggested that the 80-kDa soluble fragment may serve as a useful biomarker of disease progression for a number of cancers, including prostate, 23 gastric, 24 hepatocellular 24 and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The soluble cleaved form of E-cadherin has been observed in serum under non-pathological conditions, but increased levels of the soluble form have been detected in patient peripheral blood samples 24,54 and urine samples 55 in a variety of diseases. 21 It has been suggested that the 80-kDa soluble fragment may serve as a useful biomarker of disease progression for a number of cancers, including prostate, 23 gastric, 24 hepatocellular 24 and bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…21 It has been suggested that the 80-kDa soluble fragment may serve as a useful biomarker of disease progression for a number of cancers, including prostate, 23 gastric, 24 hepatocellular 24 and bladder cancer. 55 There has also been a correlation between tumor stage, histological grade and elevated levels of soluble E-cadherin, likely because the detection of soluble E-cadherin has been associated with increased invasiveness. 23,56,57 Although reasonable, it is currently unknown whether the detection of the C-terminal fragment of E-cadherin in the nucleus of CC-RCC correlates with increased serum level of soluble N-terminal E-cadherin fragment.…”
Section: Discussionmentioning
confidence: 99%
“…This may be considered as a reflection of increased protein excretion in urine of bladder cancer patients detected herein and reported earlier 18,35 and attributed either to leakage of serum proteins from the tumor neovasculature, or to increased turnover of bladder cancer cells. 18 If this holds true however, the specificity of the assay may be affected by the presence of renal disease, and this will have to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The bladder tumor antigen, 4 the bladder tumor antigen stat, 5 the fibrinogen/fibrin degradation products, 6 and the nuclear matrix protein-22 tests, 3,7 have been approved by the Food and Drug Administration to be used in conjunction with cystoscopy. Additional molecular assays currently being evaluated for their diagnostic/prognostic utility 2,3,8,9 are the Telomerase, 10 Immunocyt, 11 and hyaluronic acid/hyaluronidase 12,13 tests, microsatellite analysis, 14 as well as assays detecting blood group antigens, 15 carcinoembryonic antigen, 16 p53 and retinoblastoma proteins, 3 E cadherin, 17,18 and various growth factors. 9 Because of the molecular heterogeneity of these tumors, it is likely that there will be no single molecular assay that will replace cystoscopy.…”
mentioning
confidence: 99%
“…In a recent study, an 80 kDa fragment of full-length e-cadherin has been described as almost exclusively being observed in the neoplastic aspect of prostate cancer tissue (Kuefer et al, 2003). This soluble fragment has also been reported as being measurable in the serum of patients suffering from different types of adenocarcinoma (Katayama et al, 1994a;Banks et al, 1995;Gofuku et al, 1998;Velikova et al, 1998;Protheroe et al, 1999;Chan et al, 2003). In the current study, we report the accumulation of this 80 kDa fragment of e-cadherin in the serum of patients affected by prostate cancer.…”
mentioning
confidence: 99%